Synthesis and viscoelastic characterization of microstructurally aligned Silk fibroin sponges. (July 2017) - Panda, Debojyoti; Konar, Subhajit; Bajpai, Saumendra K.; Arockiarajan, A.
Abstract: Silk fibroin (SF) is a model candidate for use in tissue engineering and regenerative medicine owing to its bio-compatible mechanochemical properties. Despite numerous advances made in the fabrication of various biomimetic substrates using SF, relatively few clinical applications have been designed, primarily due to the lack of complete understanding of its constitutive properties. Here we fabricate microstructurally aligned SF sponge using the unidirectional freezing technique wherein a novel solvent-processing technique involving Acetic acid is employed, which obviates the post-treatment of the sponges to induce their water-stability. Subsequently, we quantify the anisotropic, viscoelastic response of the bulk SF sponge samples by performing a series of mechanical tests under uniaxial compression over a wide range of strain rates. Results for these uniaxial compression tests in the finite strain regime through ramp strain and ramp-relaxation loading histories applied over two orders of strain rate magnitude show that microstructural anisotropy is directly manifested in the bulk viscoelastic solid-like response. Furthermore, the experiments reveal a high degree of volume compressibility of the sponges during deformation, and also evince for their remarkable strain recovery capacity under large compressive strains during strain recovery tests. Finally, in order to predict the bulk viscoelastic material properties of the fabricated and pre-characterized SF sponges, a finite strain kinematics-based, nonlinear, continuum model developed within a thermodynamically-consistent framework in a parallel investigation, was successfully employed to capture the viscoelastic solid-like, transversely isotropic, and compressible response of the sponges macroscopically. Abstract : Graphical abstract: Abstract : Highlights: A novel technique was employed to fabricate anisotropic Silk fibroin sponges. Finite strain mechanical characterization under uniaxial compression was performed. Strain recovery capacity of the hydrated sponges under finite strains was studied. Viscoelastic model simulations were fit to data to obtain material parameters.